2005
DOI: 10.1093/jmedent/42.3.429
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Study of West Nile Virus Pathogenesis in Culex pipiens quinquefasciatus (Diptera: Culicidae)

Abstract: The ultrastructural features of West Nile virus (WNV) replication and dissemination in orally infected Culex pipiens quinquefasciatus Say were analyzed over a 25-d infection period. To investigate the effects of virus replication on membrane induction, cellular organization, and cell viability in midgut and salivary gland tissues, midguts were dissected on days 3, 7, 14, and 21, and salivary glands were collected on days 7, 14, 21, and 25 postinfection (d.p.i.) for examination by transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 38 publications
2
89
0
2
Order By: Relevance
“…aegypti infected with Semliki Forest virus (Mims et al, 1966), in Culiseta melanura infected with eastern equine encephalitis virus (Weaver et al, 1988), and in Aedes albopictus infected with Sindbis virus (Bowers et al, 2003). Long-term West Nile virus infection has also been shown to induce cell death in the salivary glands of Culex pipiens quinquefasciatus (Girard et al, 2005) and the same group later suggested that this late pathology affected transmission rates (Girard et al, 2007). Recently it has been shown that a lab-derived strain of Culex pipiens pipiens was refractory to infection with West Nile virus, and that infection with this virus caused extensive cell death in the midgut epithelial cells of these mosquitoes (Vaidyanathan and Scott, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…aegypti infected with Semliki Forest virus (Mims et al, 1966), in Culiseta melanura infected with eastern equine encephalitis virus (Weaver et al, 1988), and in Aedes albopictus infected with Sindbis virus (Bowers et al, 2003). Long-term West Nile virus infection has also been shown to induce cell death in the salivary glands of Culex pipiens quinquefasciatus (Girard et al, 2005) and the same group later suggested that this late pathology affected transmission rates (Girard et al, 2007). Recently it has been shown that a lab-derived strain of Culex pipiens pipiens was refractory to infection with West Nile virus, and that infection with this virus caused extensive cell death in the midgut epithelial cells of these mosquitoes (Vaidyanathan and Scott, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Arbovirus infection often leads to apoptosis in vertebrate cells, but mosquito cells usually undergo nonlytic, persistent arbovirus infections (16)(17)(18)(19)(20), even though A. aegypti cells have a functional apoptosis pathway that largely resembles that of Drosophila melanogaster (21)(22)(23). Pathological effects resulting from arbovirus infection in mosquitoes have been reported in a few cases (24)(25)(26)(27), but arbovirus infections are generally thought to have a minimal effect on mosquito vectors, although that assumption has been challenged (28). However, there have been a small handful of reports of apoptosis correlating with resistance of mosquitoes to infection by arboviruses.…”
mentioning
confidence: 99%
“…However, there have been a small handful of reports of apoptosis correlating with resistance of mosquitoes to infection by arboviruses. Apoptosis observed in salivary glands of Culex quinquefasciatus infected with West Nile virus has been proposed to be a defense against infection (24,29,30). In addition, West Nile virus infection in a refractory strain of C. quinquefasciatus correlated with extensive cell death in midgut tissue (31).…”
mentioning
confidence: 99%
“…The mean WNV titer in the recipients was 4.70 Ϯ 2.0 log 10 TCID 50 per mosquito. Because this result is similar to titers attained in orally infected mosquitoes at 14 days p.i., a time when virus is observed in saliva (24) and when 93% of females can transmit up to 5.29 log 10 plaque-forming units of WNV (11), we believe that many of the infected recipient mosquitoes would have been capable of transmitting WNV. Infections with WNV can be generated by inoculation of very low titers of virus, for example, crows can be infected by mosquitoes that probe but fail to engorge (25).…”
Section: Resultsmentioning
confidence: 98%